The village of widows - Ettet, Ravi Shankar (London Black Swan, 2004)
When a diplomat at the Madagascan Embassy in Delhi is stabbed to death in seemingly scandalous and mysterious circumstances, the ambassador asks his old friend and fellow chess enthusiast, Jay Samorin, to help find the murderer as quickly and discretely as possible
1
Keywords: Police -- India -- iction; Police